2019
DOI: 10.9767/bcrec.14.3.2939.502-512
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Sodalite from Indonesian Kaolin for Adsorption of Pb2+ Solution, Kinetics, and Isotherm Approach

Abstract: Indonesian kaolin was used as precursor for synthesis of sodalite. Synthesis parameters were optimized by varying the Si/Al ratios, stirring and aging conditions, and water composition. X-ray diffraction (XRD), Fourier Transform Infra Red (FTIR), Scanning Electron Microscope-Energy Dispersive Xray (SEM-EDX), and Particle Size Analyzer (PSA) were used to characterize sodalite. The potential of sodalite as adsorbent for heavy metal Pb 2+ ions removal from waste water was investigated in this work. The uptake ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…Although the initial molar composition of sodalite was similar, changing the temperature and the time for crystallization enhanced the adsorption capacity of Pb 2+ . The capacity of sodalite adsorption in this study was greater than that in our previously reported studies, at 97.15 mg/g [16]. The formation of stable silicate particles was crucial to ensure efficient interaction with CTABr for the formation of larger mesopore cavities.…”
Section: Adsorption and Kinetic Study Of Pb 2+contrasting
confidence: 61%
See 1 more Smart Citation
“…Although the initial molar composition of sodalite was similar, changing the temperature and the time for crystallization enhanced the adsorption capacity of Pb 2+ . The capacity of sodalite adsorption in this study was greater than that in our previously reported studies, at 97.15 mg/g [16]. The formation of stable silicate particles was crucial to ensure efficient interaction with CTABr for the formation of larger mesopore cavities.…”
Section: Adsorption and Kinetic Study Of Pb 2+contrasting
confidence: 61%
“…Zeolite has a uniform pore structure and high surface area to ensure efficient diffusion and adsorption of large pollutants [14,15]. Sodalite is a zeolite with good adsorption ability [16] that can be used as a catalyst or catalyst support [17].…”
Section: Introductionmentioning
confidence: 99%
“…Methylene blue (MB) is an example of cationic synthetic dye commonly used in the textile and pharmaceutical industry [1]. Exposure to excessive MB could cause harmful ef-Clay minerals like bentonite, palygorskite, and kaolinite have received great interest either as a catalyst or pollutant adsorbent due to its non-toxicity, inexpensive and high availability [3,5,6]. Malaysia has approximately 112 million tons of kaolinite reserve [7,8] with a total export value of Malaysian Ringgit 26 million (approximately USD 6 million) in 2013 [8].…”
Section: Introductionmentioning
confidence: 99%